Subversion, Substance, & Soteriology: The Redeeming Womb in Julian of Norwich’s Revelations - Carroll, Gabriella (Lumen et Vita, 2017)
This essay examines how the soteriology in Julian of Norwich’s work, Revelations of Divine Love, proves doubly radical, for it disrupts the traditional metanarratives of the Middle Ages not only by calling for a universal salvation, but also by revealing how this salvation is rooted in the female body—a stance that prefigures the postmodern theological movement. The first part of this essay offers an overview of postmodern theology as a “new kind of consciousness,” and how Julian facilitates this new awareness through her use of (both physical and social) bodily images in her text. During the Middle Ages, the female body was viewed as a “category of social pollution,” and thus something to be feared, regulated, and controlled. However, through her image of the hazelnut, Julian identifies both the importance and necessity of the female body for the salvation of humanity, as she reveals Mary’s womb as the root of Christian salvation. The second part of this essay offers “case studies” of how Julian employs this “redeeming womb” narrative throughout the rest of her text. Drawing upon the Parable of the Lord & Servant, Julian demonstrates how, if Christ had not fallen into the depths of the Virgin’s womb, there would be no resurrection, and thus no universal salvation. By “falling” into Mary’s womb, Christ was thus able to return our “failed” sensual soul back to God in ultimate, essential union. Through her Revelations, Julian ultimately reverses the ideological coding of her time: the traditionally deemed “inferiority” and “impurity” of the female body is completely inverted, as she depicts the female body so important and valuable that Christian salvation is rooted in its substance. It is through this “reversal” that Julian can be seen as a prefiguring founder of the postmodern theological movement and, more specifically, the mother of postmodern feminist theology.